Implementation of Guidance and Parenting in the Mental Preparation of Military Academy Cadet Leadership Level IV in Entering the Indonesian Army Organic Unit - Joko Prio Suseno; Umi Listyaningsih; Ahmad Maryudi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2022)
The educational process at the Military Academy refers to the regulations of the Ministry of Education and Culture as well as the Ministry of Defense. Military Academy cadets are not only required to have academic abilities, but also have to have physical endurance, good attitudes, and behavior, and characters that reflect the leadership values. The Military Academy which has the task of creating the future of Indonesian Army Military Leaders is managed by combining conventional learning methods and providing guidance and parenting (Bimbingan dan Pengasuhan/Bimsuh). Bimsuh is intended to lead cadets to understand, explore, and implement the values of leadership, the character of a warrior, and the spirit of Sapta Marga by observing, examining, and imitating the Caregivers before entering the Indonesian Army Organic Unit. This study analyzes the influence of Bimsuh on the leadership mentality of Level IV cadets in entering the Indonesian Army Organic Unit. This study uses a qualitative approach with caregivers, managers, and cadets as the informants and a quick survey via google form to cadets. In addition to the primary data, the analysis also came from secondary data, such as the Military Academy roadmap, curriculum, strategic plans for the Cadets Regiment, and Military Teacher Teaching Materials. The results of the study showed that the duration of the implementation of Bimsuh was more than the Lesson Hours. This is different from the existing curriculum with 7 percent teaching hours for Bimsuh. Level IV Military Academy cadets expect to have longer hours of Bimsuh to explore the experiences of Caregivers while serving in the Army Organic Unit. Youth leadership mentality is influenced by Bimsuh which is oriented towards achievement by developing creative and innovative thinking. Guidance and parenting with pressure, sanctions, and authoritarian approaches are not effective if they are not carried out in accordance with the achievement-oriented approach. Level IV cadets feel that they have the instilled leadership values so far. However, the cadets still lack self-confidence, lack the courage to make decisions quickly, and in taking risks. This condition is also experienced by the Caregivers because they do not have experience. Knowledge, skills, and experience while in the Military Academy as capital to adapt quickly in the Indonesian Army Organic Unit.